Supervisor telepressure and work-family conflict: the moderating role of meaningful work - Stevens, Shalyn C., author; Crain, Tori L., advisor; Chen, Adela J., committee member; Fisher, Gwenith G., committee member; Harman, Jennifer J., committee member (Colorado State University. Libraries, 2018)
Workplace telepressure, the preoccupation and urge to respond to incoming work-related messages, is an emerging construct in the organizational science literature. Relatively few studies have examined antecedents and outcomes of telepressure, in addition to conditions under which experiences of telepressure may be intensified. Using a cross-sectional sample, the present study evaluates supervisor experiences of telepressure, drawing on Kahn and Byosiere's (1992) elaboration of the Institute for Social Research (ISR) model of occupational stress. Specifically, telepressure is tested as a mediator of the hypothesized positive relationship between organizational after-hours response expectations and work-to-family conflict. Additionally, I propose that the meaningfulness of one's work may actually heighten feelings of telepressure. Therefore, this study also considers the potential "dark side" of meaningful work, and tests it as a moderator of the organizational after-hours response expectations–telepressure relationship. Results demonstrate support for three of the four hypotheses. Specifically, organizational response expectations positively related to feelings of telepressure, telepressure also positively related to all three dimensions of work-to-family conflict (i.e., time-based, strain-based, and behavior-based), and finally, telepressure mediated the relationship between response expectations and work-to-family conflict. This study did not find support for the moderating role of meaningful work. Theoretical and practical implications of this work are discussed.
Keywords: telepressure; meaningful work; work-family conflict